The book of phobias & manias : a history of obsession - Summerscale, Kate, 1965- (Penguin Books, 2022)
"The Book of Phobias and Manias is a thrilling compendium of 99 obsessions that have shaped us all, the rare and the familiar, from ablutophobia (a horror of washing) to syllogomania (a compulsion to hoard) to zoophobia (a fear of animals)"--